Struktur APBD Terhadap Keuangan Daerah Dan Pertumbuhan Ekonomi Di Sumatera Utara - Panjaitan, Indy Tiffany; Ramadhani Br. Sibarani, Nissa Nur; Ritonga, Syaiful Abdi (LPPM Universitas Labuhanbatu, 2022)
Abstract this study aims to evaluate whether the Medan city government has used the budget economically, efficiently, and effectively (value for money), then the budget analysis on regional spending, among others, to determine the occurrence of variance spending, the difference or the difference between the realization of spending with the budget. To determine the growth rate of spending, the development of spending from year to year. To determine the Harmony of spending or balance between spending in the budget function as a means of distribution, allocation and stabilization by the Medan City Government. To measure the level of efficiency of the use of the Medan city government budget in realizing regional spending.. The Data collected and used in this study are secondary data obtained from official documents, namely budget realization reports relating to the budget performance of the Medan City Government from 2016 to 2020 obtained from the Medan City Regional Financial and Asset Management Agency (BPKAD).